(untitled) (Research, Society and Development, 2022)
The objective of this study was to create and validate an educational material on healthy eating, which will support health professionals in conducting their consultations with adolescents who suffer from mental disorders. It is methodological research emphasizing the development, evaluation, and improvement of educational material. The process for the development of this booklet was outlined in 3 stages, construction of the booklet, evaluation by the judges (professionals and adolescents), and validation. According to established criteria, data were collected through an evaluation instrument with eight judges. A content evaluation was performed using a Likert-type scale. The analysis was performed after tabulating the data in an Excel spreadsheet, where the adequacy and relevance of the content were determined, among the judges, through the content validity index (CVI), with a minimum of 80%, and carrying out a pilot test with teenagers. The judges in the areas of Nutrition, Psychology, and Nursing made it possible to validate the material with a global Content Validation Index (CVI) that ranged from 0.88 to 1.00 in 8 items and, among adolescents, a minimum agreement of 0 was obtained 0.81 among the items evaluated. There were suggestions and all were accepted. The educational booklet proved to be valid and reliable material to be used by health professionals in guidelines on diet and mental health, with a satisfactory agreement rate.